Contrasting Epidemiology and Clinicopathology of Female Breast Cancer in Asians vs the US Population - Lin, Ching-Hung; Yap, Yoon Sim; Lee, Kyung-Hun; Im, Seock-Ah; Naito, Yoichi; Yeo, Winnie; Ueno, Takayuki; Kwong, Ava; Li, Huiping; Huang, Shu-Min; Leung, Roland; Han, Wonshik; et al. (JNCI : Journal of the National Cancer Institute, 2019)
Abstract Background The incidence of breast cancer among younger East Asian women has been increasing rapidly over recent decades. This international collaborative study systemically compared the differences in age-specific incidences and pathological characteristics of breast cancer in East Asian women and women of predominantly European ancestry. Methods We excerpted analytic data from six national cancer registries (979 675 cases) and eight hospitals (18 008 cases) in East Asian countries and/or regions and, for comparisons, from the US Surveillance, Epidemiology, and End Results program database. Linear regression analyses of age-specific incidences of female breast cancer and logistic regression analyses of age-specific pathological characteristics of breast cancer were performed. All statistical tests were two-sided. Results Unlike female colorectal cancer, the age-specific incidences of breast cancer among East Asian women aged 59 years and younger increased disproportionally over recent decades relative to rates in US contemporaries. For years 2010–2014, the estimated age-specific probability of estrogen receptor positivity increased with age in American patients, whereas that of triple-negative breast cancer (TNBC) declined with age. No similar trends were evident in East Asian patients; their probability of estrogen receptor positivity at age 40–49 years was statistically significantly higher (odd ratio [OR] = 1.50, 95% confidence interval [CI] = 1.36 to 1.67, P < .001) and of TNBC was statistically significantly lower (OR = 0.79, 95% CI = 0.71 to 0.88, P < .001), whereas the probability of ER positivity at age 50–59 years was statistically significantly lower (OR = 0.88, 95% CI = 0.828 to 0.95, P < .001). Subgroup analyses of US Surveillance, Epidemiology, and End Results data showed similarly distinct patterns between East Asian American and white American patients. Conclusions Contrasting age-specific incidences and pathological characteristics of breast cancer between East Asian and American women, as well as between East Asian Americans and white Americans, suggests racial differences in the biology.